Linking winter wheat (Triticum aestivum L) root traits and root water uptake with electrical resistivity tomography - Huijie Gu; Yanzhe Wang; Luca Peruzzo; Baoru Li; Yang Lu; Xiuwei Liu (Agricultural Water Management)
Electrical resistivity tomography (ERT) is extensively employed for monitoring soil water content (SWC) in agricultural fields. However, the direct impacts of roots and the indirect effects of root water uptake on soil electrical resistivity (ER) have been largely neglected. Furthermore, the application of ERT technology for precise measurements of crop roots in various conditions (such as cultivars and irrigations regimes) remains unexplored. This study, therefore, utilized buried fresh root experiments, soil pots, and field-irrigation trials with different winter wheat (Triticum aestivum L.) cultivars to examine the influence of fresh crop roots on ER and assess ERT’s capability to characterize root uptake and the root system size. The findings from the buried root and pot experiments demonstrated that fresh root addition significantly reduced the ER of mixed soil (sand and loam are mixed in a ratio of 1:5) when the SWC was below 0.24 cm3 cm−3. However, in loam soil, fresh root addition did not significantly decrease the ER. Pot experiments revealed strong positive correlations between root surface area and soil ER (R2 = 0.78, P < 0.001), suggesting that the increase in soil ER due to root absorption greatly outweighs the reduction caused by the roots themselves. Field experiments conducted during the grain-filling phase, when root size was stable, showed significant differences in soil ER changes (defined as the difference between two consecutive ER measurements) among winter wheat cultivars in both shallow (0–40 cm) and deep (40–100 cm) soil layers under various irrigation treatments. It was observed that wheat tends to utilize deep soil moisture in later growth stages, even with sufficient water conditions. Further analysis indicated that ER changes were positively correlated (R2 > 34, n = 50) with root surface area density (RSAD) in the 0–100 cm soil layer, particularly showing a stronger correlation with RSAD in the deep soil layer compared to the shallow layer under deficit irrigation (R2=0.65 vs. R2=0.23). In conclusion, ERT effectively characterizes the differences in root water uptake as well as root system size, especially focusing on deep roots among cultivars under various irrigation regimes.